Assisting Young Children Caught in Disasters Multidisciplinary Perspectives and Interventions (Educating the Young Child, Advances in Theory and Research, Implications for Practice,, 2018)
This volume discusses 14 different types of disasters and their implications on the social, emotional and academic development of young children, from birth through age eight. It focuses on human-related crises and disasters such as community violence exposure; war and terrorism; life in military families; child trafficking; parent migration; radiation disasters; HIV/AIDS; and poverty. The environment-related disasters addressed in this book include hunger; hurricanes; earthquakes; frostbites; wildfires; and tornadoes. The volume includes suggestions for interventions, such as using picture books with young children in coping with natural disasters and human crises. In addition, each chapter provides research-based strategies for early childhood and related professionals to be used in the classroom. Many children in our world today experience some type of disasters and/or crises. These crises or disasters can either be human- or environment-related and can interrupt children's daily lives. They often negatively impact children's development, education, and safety. Bringing together authors representing a variety of countries including Australia, Canada, China, Finland, Haiti, Hungary, Kenya, USA, and Zimbabwe, this book provides truly global perspectives on the various types of disasters and their implications for our work with young children. .